Mevalonate kinase gene polymorphisms in ankylosing spondylitis patients: A cross-sectional study - Fatih Yıldız; Suzan Dinkçi; Eren Erken (Archives of Rheumatology, 2023)
Objectives: This study aimed to investigate the potential effect of the mevalonate kinase (MVK) gene polymorphisms on the pathogenesis and clinical findings in ankylosing spondylitis (AS) patients. Patients and methods: This cross-sectional study was conducted with 103 participants (63 males, 40 females) between January 2013 and January 2014. Of these, 51 (32 males, 19 females; mean age: 37.3±10.2 years; range, 19 to 60 years) were adult AS patients who met the 1984 Modified New York Criteria, and 52 (31 males, 21 females; mean age: 33.8±12 years; range, 19 to 60 years) were healthy volunteers with similar demographics. MVK gene analysis was performed using polymerase chain reaction sequencing by isolating deoxyribonucleic acids from peripheral blood samples. We determined serum immunoglobulin (Ig)D levels using radial immunodiffusion. We performed physical examinations on the AS patients. The Bath Ankylosing Spondylitis Disease Activity Index and the Bath Ankylosing Spondylitis Functional Index forms were filled and erythrocyte sedimentation rate, C-reactive protein, and IgD levels were recorded. Results: There was no statistically significant difference in the mean age between the groups (p=0.121). The frequency of symptomatic single nucleotide polymorphisms (SNPs), c.769-38 C>T heterozygous, c.769-7 T>G heterozygous, and c.769-38 C>T homozygous were similar between the groups (15/15; p=0.646). Nonsymptomatic SNPs were more common in the patient group, but the difference was not significant (83/58; p>0.05). The rate of having an MVK gene polymorphism was 36 (70.6%) in the AS compared to the 33 (63.4%) in the control group (p>0.05). There were no associations in clinical findings between the AS patients with or without MVK gene polymorphisms. New heterozygous SNPs, I56V A>G, E281D G>D, V80I G>A, and C173Y G>A, were present in four AS patients. Conclusion: The frequency of MVK gene polymorphisms was higher in AS patients than in healthy controls. But there was no statistically significant difference. We determined no effect of the present polymorphisms on AS clinical and laboratory findings.